Health services use among children diagnosed with medium-chain acyl-CoA dehydrogenase deficiency through newborn screening: a cohort study in Ontario, Canada - Maria D. Karaceper; Sara D. Khangura; Kumanan Wilson; Doug Coyle; Marni Brownell; Christine Davies; Linda Dodds; Annette Feigenbaum; Deshayne B. Fell; Scott D. Grosse; Astrid Guttmann; Steven Hawken; et al. (Orphanet Journal of Rare Diseases, 2019)
Abstract Background We describe early health services utilization for children diagnosed with medium-chain acyl-CoA dehydrogenase (MCAD) deficiency through newborn screening in Ontario, Canada, relative to a screen negative comparison cohort. Methods Eligible children were identified via newborn screening between April 1, 2006 and March 31, 2010. Age-stratified rates of physician encounters, emergency department (ED) visits and inpatient hospitalizations to March 31, 2012 were compared using incidence rate ratios (IRR) and incidence rate differences (IRD). We used negative binomial regression to adjust IRRs for sex, gestational age, birth weight, socioeconomic status and rural/urban residence. Results Throughout the first few years of life, children with MCAD deficiency (n = 40) experienced statistically significantly higher rates of physician encounters, ED visits, and hospital stays compared with the screen negative cohort. The highest rates of ED visits and hospitalizations in the MCAD deficiency cohort occurred from 6 months to 2 years of age (ED use: 2.1–2.5 visits per child per year; hospitalization: 0.5–0.6 visits per child per year), after which rates gradually declined. Conclusions This study confirms that young children with MCAD deficiency use health services more frequently than the general population throughout the first few years of life. Rates of service use in this population gradually diminish after 24 months of age.